Respuesta :

Answer:

a) -10

b) 2

Step-by-step explanation:

x=-2

y=3

so just substitute that in for each equation.

a)

(-2)2 + (-3)2 =

-2 x 2 = -4

( negative x negative = positive, positive x negative = negative, positive x positive = positive)

-3 x 2 = -6

-4 + -6 = -10

(think of subtraction as adding a negative number)

-10 is your answer

b) ((-2) + (3))2 =

solve the thing in parenthesis first (PEMDAS)

-2 + 3 = 1

now 1 is the parenthesis making the equation (1)2

1 x 2 = 2

2 is your answer

1. -10. 2. -10 I think that is the answer